Presidential term limits and fiscal policy in African countries†. (24th November 2018) - Yogo, Urbain Thierry; Keneck Massil, Joseph
Abstract: This paper assesses the effect of the attempt by an incumbent to amend the section of the constitution related to the presidential term limits on fiscal policy. Specifically, we test the hypothesis that the process of modifying the constitution to run for a third term leads the incumbent to increase government spending as a tool for political patronage. Using a sample of 30 African countries over the period 1990–2010, our findings indicate an increase in government spending during the term in which the constitution was amended. In addition, we find evidence of the exacerbation of the political budget cycle during periods of expansion. However, this effect is not robust to alternative estimation strategies, including matching techniques. From the policy perspective, this study suggests that it is worth watching out not only for elections but also for constitutional changes that are a catalyst of fiscal indiscipline and can further weaken institutions that are positively correlated with countercyclical fiscal policies.